Complexities of Productivity Policies in the Finnish Public Sector: Knowing How to Do More with Less?. (16th September 2015) - Kork, Anna‐Aurora; Mänttäri, Pietu; Vakkuri, Jarmo
Abstract: This paper examines public sector productivity policies as complexities between what is 'known' in policy principles and what is 'done' in everyday policy practice. Such complexities are explored in two productivity policy cases within Finnish local government: municipal amalgamations, and the low‐threshold concept of healthcare service. Utilising quantitative and qualitative data from Finnish local government the paper demonstrates the tensions between productivity policy principles, interpretations for productivity improvement (' knowing ') and final outcomes for actually applying (' doing ') productivity policy. The paper argues in favour of a new understanding for the research and practice of public policy and management.